PROSES BERPIKIR MAHASISWA DALAM MEMECAHKAN MASALAH PEMBUKTIAN GRUP BERDASARKAN LANGKAH POLYA - Muliawati, Novita Eka (STKIP PGRI Tulungagung, 2018)
This research is aimed to describes the thinking process of students in solving the proof of group problems based on Polyaâ??s steps reviewed on mathematical ability. This descriptive qualitative research is conducted using tests and interview method to 3 students were selected from 31 students 6th semester of Mathematics Education Study Program, STKIP PGRI Tulungaung in the period of 2017/2018. The selected criteria for research subjects based on the result of the mathematical ability tests related to algebraic structures. The result shows that the thinking process of students in solving the proof of group problems based on Polyaâ??s steps are high-ability students are able to prove the group appropriately, middle-ability students are able to prove the group appropriately but with several revision processes, and less-ability students haven't been able to prove the group correctly.Â Keywords: thinking process, proof group, polya steps